Analisis Perbandingan Kualitas Citra Hasil Steganografi DCT dan LSB Berdasarkan Parameter RMSE dan PSNR - Putra, I Putu Krisnawan; Supriana, I Wayan (Jurnal Nasional Teknologi Informasi dan Aplikasnya, 2024)
Steganography is a technique of hiding secret messages in digital media, one of the digital media that is often used is images. Two commonly used steganography methods are DCT (Discrete Cosine Transform) and LSB (Least Significant Bit). This research aims to analyze and compare the image quality of DCT and LSB steganography results based on RMSE (Root Mean Square Error) and PSNR (Peak Signal to Noise Ratio) parameters. DCT and LSB methods are implemented on several images with several variations of secret messages. RMSE and PSNR values are calculated for each stego image and analyzed to see which method produces better image quality. The results show that the LSB method produces lower RMSE values and higher PSNR values compared to the DCT method on all tested images. This shows that the LSB method is significantly better in maintaining the quality of the stego image compared to the DCT method.